Differences in the endophytic microbiome of olive cultivars infected by xylella fastidiosa across seasons - Giampetruzzi, Annalisa (2020)
The dynamics of Xylella fastidiosa infections in the context of the endophytic microbiome was studied in field-grown plants of the susceptible and resistant olive cultivars Kalamata and FS17. Whole metagenome shotgun sequencing (WMSS) coupled with 16S/ITS rRNA gene sequencing was carried out on the same trees at two different stages of the infections: In Spring 2017 when plants were almost symptomless and in Autumn 2018 when the trees of the susceptible cultivar clearly showed desiccations. The progression of the infections detected in both cultivars clearly unraveled that Xylella tends to occupy the whole ecological niche and suppresses the diversity of the endophytic microbiome. However, this trend was mitigated in the resistant cultivar FS17, harboring lower population sizes and therefore lower Xylella average abundance ratio over total bacteria, and a higher α-diversity. Host cultivar had a negligible effect on the community composition and no clear associations of a single taxon or microbial consortia with the resistance cultivar were found with both sequencing approaches, suggesting that the mechanisms of resistance likely reside on factors that are independent of the microbiome structure. Overall, Proteobacteria, Actinobacteria, Firmicutes, and Bacteriodetes dominated the bacterial microbiome while Ascomycota and Basidiomycota those of Fungi.